Higher risk of opioid-induced respiratory depression in children with neurodevelopmental disability: a retrospective cohort study of 12 904 patients - Jay, M.A.; Thomas, B.M.; Nandi, R; Howard, R.F. (British journal of anaesthesia : BJA, 2017)
Children with neurodevelopmental disabilities may be at risk of opioid-induced respiratory depression. We aimed to quantify the risks and effectiveness of morphine nurse-controlled analgesia (morphine-NCA) for postoperative pain in children with neurodevelopmental disabilities. We carried out a retrospective cohort study of 12 904 children who received postoperative i.v. morphine-NCA. Subjects were divided into a neurodevelopmental disability group and a control group. Rates of clinical satisfaction, respiratory depression, and serious adverse events were obtained, and statistical analysis, including multilevel logistic regression using Bayesian inference, was performed. Of 12 904 patients, 2390 (19%) had neurodevelopmental disabilities. There were 88 instances of respiratory depression and 52 serious adverse events; there were no opioid-related deaths. The cumulative incidence of respiratory depression in the neurodevelopmental disability group was 1.09% vs 0.59% in the control group [odds ratio 1.8 (98% chance that the true odds ratio was >1)]. A significant interaction between postoperative morphine dose and neurodevelopmental disabilities was observed, with higher risk of respiratory depression with increasing dose. Satisfaction with morphine-NCA was very high overall, although children with neurodevelopmental disabilities were 1% more likely to have infusions rated as fair or poor (3.3 vs 2.1%, χ2P<0.001). Children with neurodevelopmental disabilities were 1.8 times more likely to suffer respiratory depression, absolute risk difference 0.5%; opioid-induced respiratory depression in this group may relate to increased sensitivity to dose-relate respiratory effects of morphine. Morphine-NCA as described was an acceptable technique for children with and without neurodevelopmental disabilities.